# Basic Algebra 2 by Nathan Jacobson By Nathan Jacobson

Similar elementary books

Beginner's Basque

This name incorporates a ebook and a couple of audio CDs. Basque is the language spoken via the Basque those who stay within the Pyrenees in North primary Spain and the adjacent area of south west France. it's also spoken through many immigrant groups worldwide together with the united states, Venezuela, Argentina, Mexico and Colombia.

Elementary Algebra

Easy Algebra is a piece textual content that covers the conventional issues studied in a contemporary trouble-free algebra path. it's meant for college kids who (1) haven't any publicity to basic algebra, (2) have formerly had an uncongenial adventure with trouble-free algebra, or (3) have to assessment algebraic strategies and methods.

Additional info for Basic Algebra 2

Example text

But then whatever the choice of x and y, + cy = ar x + asy = a(r x + sy) Because rx + sy is an integer, this says that a I (bx + cy), as desired. 2 extends by induction to sums of more than two terms. That is, if a I bk fork = 1, 2, ... , n, then a I (b1x1 + bzxz + · · · + bnxn) for all integers x 1, x 2 , ••. , Xn. The few details needed for the proof are so straightforward that we omit them. If a and b are arbitrary integers, then an integer d is said to be a common divisor of a and b if both d I a and d I b.

Because 6 is the largest of these integers, it follows that gcd( -12, 30) = 6. In the same way, we can show that gcd( -5, 5) = 5 gcd(8 , 17) = 1 gcd( -8, -36) = 4 The next theorem indicates that gcd(a, b) can be represented as a linear combination of a and b. ) This is illustrated by, say, gcd( -12, 30) = 6 = (-12)2 + 30 · 1 or gcd( -8, -36) = 4 = (-8)4 + (-36)( -1) Now for the theorem. 3. Given integers a and b, not both of which are zero, there exist integers x and y such that gcd(a, b)= ax+ by Proof.

Inasmuch as a I c and b 1 c, integers rands can be found such that c = ar = bs. Now the relation gcd(a, b)= 1 allows us to write 1 =ax+ by for some choice of integers x andy. Multiplying the last equation by c, it appears that c = c · 1 = c(ax +by) = acx +bey If the appropriate substitutions are now made on the right-hand side, then c = a(bs)x + b(ar)y = ab(sx + ry) or, as a divisibility statement, ab I c. 24 ELEMENTARY NUMBER THEORY Our next result seems mild enough, but is of fundamental importance.